Improving Students Activity and Students Learning Outcomes by Using NHT (Numbered Heads Together) with PBI (Problem Based Instruction) - Qurrota A Yun (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to describe the students activities in using numbered heads together (NHT) with problem based instruction (PBI) learning model. To describe the students learning outcomes in using numbered heads together (NHT) with problem based instruction (PBI) learning model. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs Miftahul Ulum Kepanjen. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: NHT,  PBI, students activity, and students learning outcomes